Influence of the excess Al content on memory behaviors of Worm devices based on sputtered Al-rich aluminum oxide thin films - Liu, Z. (2015)
Reactive sputtering has been used to synthesize Al-rich Al2O3 thin films. After post-deposition thermal annealing, the excess Al content forms Al nanocrystals (nc-Al) which are dispersed in the Al2O3 matrix. In the Al/Al-rich Al2O3/p-Si structure, the current conduction which follows a Schottky emission process can be greatly enhanced by a charging process with negative voltage pulses and then maintained for considerable duration, realizing write-once-read-many-times (WORM) memory behaviors. The current conduction enhancement is attributed to the reduction of effective Schottky barrier caused by charging-induced hole trapping in the nc-Al related defects near the oxide/p-Si interface. It is found that the sample with lower concentration of nc-Al has a larger memory window due to the lower initial current. In addition, the retention is also better since the release of trapped charges is more difficult with less nc-Al related leakage paths present in the oxide film. The concentration of excess Al content in the Al-rich Al2O3 thin film can be optimized to achieve large memory windows as well as good retention characteristics in the associated WORM memory devices.